Review: Adaptation of Beneficial Propionibacteria, Lactobacilli, and Bifidobacteria Improves Tolerance Toward Technological and Digestive Stresses - Gaucher, Floriane; Bonnassie, Sylvie; Rabah, Houem; Marchand, Pierre; Blanc, Philippe; Jeantet, Romain; Jan, Gwénaël (Frontiers in Microbiology, 2019)
This review deals with beneficial bacteria, with a focus on lactobacilli, propionibacteria, and bifidobacteria. As being recognized as beneficial bacteria, they are consumed as probiotics in various food products. Some may also be used as starters in food fermentation. In either case, these bacteria may be exposed to various environmental stresses during industrial production steps, including drying and storage, and during the digestion process. In accordance with their adaptation to harsh environmental conditions, they possess adaptation mechanisms, which can be induced by pretreatments. Adaptive mechanisms include accumulation of compatible solutes and of energy storage compounds, which can be largely modulated by the culture conditions. They also include the regulation of energy production pathways, as well as the modulation of the cell envelop, i.e., membrane, cell wall, surface layers, and exopolysaccharides. They finally lead to the overexpression of molecular chaperones and of stress-responsive proteases. Triggering these adaptive mechanisms can improve the resistance of beneficial bacteria toward technological and digestive stresses. This opens new perspectives for the improvement of industrial processes efficiency with regard to the survival of beneficial bacteria. However, this bibliographical survey evidenced that adaptive responses are strain-dependent, so that growth and adaptation should be optimized case-by-case.